Effect of Feed Supplement and Probiotics on Growth Performance of Japanese Quails - Gupta, N.K.; Shrivastava, A.K.; Praveen, P.K.; Ganguly, S. (Indian Journal of Animal Nutrition, 2018)
The study was conducted on 120 day-old Japanese quail chicks under deep litter system which were randomly divided into four group viz., T1, T2, T3 and T4 of thirty birds each. Group T1, T2 and T3 were given feed supplement, probiotic and their combination, respectively along with basal diet and the group T4 was kept ascontrol. At 6 week age, higher (P